1976
DOI: 10.1080/00039896.1976.10667226
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Effects of Occupational Exposure to an Epoxy Resin System

Abstract: A standardized respiratory questionnaire and pulmonary function tests were used to examine thirty-four employees of a snow-ski manufacturing plant, including twenty-five workers who were exposed to an epoxy resin system containing the amine hardener 3-dimethylamino propylamine (3-DMAPA). Maximum expiratory flow-volume curves were obtained on Monday and Thursday, before and after each shift, and FVC, FEV1.0, MEF50%, and MEF25% were caculated. Environmental measurements of the total amine levels were found to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Exposure to many other chemical compounds in industries, such as chloramine T, a sterilizing agent used in the food and beverage industry [127], persulphate salts used among hairdressers [128], diazonium salts in photo-copying process [129], reactive dyes in textile industry [130] and azobisformamide in plastics industry can give rise to occupational asthma [131]. It will not be possible to discuss each one of them in detail.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Exposure to many other chemical compounds in industries, such as chloramine T, a sterilizing agent used in the food and beverage industry [127], persulphate salts used among hairdressers [128], diazonium salts in photo-copying process [129], reactive dyes in textile industry [130] and azobisformamide in plastics industry can give rise to occupational asthma [131]. It will not be possible to discuss each one of them in detail.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Seven cases of amine‐related OR (or OR + OA) were finally documented in this series. With the exception of 3‐N,N‐dimethylaminopropylamine (3DMAPA) [Sargent et al, ], the amines responsible for a positive NPT in this series have not been previously reported to be responsible for OR/OA. These amines were tested because all amines must be suspected to be possible asthmagens: many amines are known to be OA inducers (Table ) and quantitative structure‐activity relationships have shown an association between amines and OA hazard [Jarvis et al, ].…”
Section: Discussionmentioning
confidence: 97%
“…For 3DMAPA (Fig. e), Sargent et al [] reported significant decreases in lung function in workers of a snow‐ski manufacturing plant with the highest exposure to this amine, used as an epoxy resin hardener.…”
Section: Discussionmentioning
confidence: 99%
“…Le colmatage des microfissures est actuellement réalisé a l'aide de résines synthétiques. Toutefois, ces composés sont toxiques et polluants, et nécessitent un renouvellement régulier du traitement [1][2][3] ; ce qui augmente le coût et l'impact environnemental générés par ces réparations. L'agent de réparation du futur pourraitêtre la calcite biogénérée, un matériau durable et naturel.…”
Section: Introductionunclassified